Screening of latent tuberculosis infection among patients with diabetes mellitus from a high-burden area in Brazil - Torres, Amanda Vital; Corrêa, Raquel da Silva; Bevilacqua, Maria de Fátima; do Prado, Luana Cristina França; Bandeira, Flavia Miranda Gomes de Constantino; Rodrigues, Luciana Silva; Gomes, Marilia Brito (Frontiers in Clinical Diabetes and Healthcare, 2022)
Although several cohort studies have raised the important association between diabetes mellitus (DM) and latent tuberculosis infection (LTBI), evidences are limited and controversial. Furthermore, it is well documented that the poor glycemic control may exacerbate the risk for active TB. Thus, the monitoring of diabetic patients living in high-incidence areas for TB is an important concern in views of available diagnostic tests for LTBI. In this cross-sectional study, we estimate the association of DM and LTBI among diabetic patients classified as type-1 DM (T1D) or type-2 DM (T2D) living in Rio de Janeiro, RJ, Brazil – considered a high TB burden region of these country. Non-DM volunteers were included as endemic area healthy controls. All participants were screened for DM using glycosylated-hemoglobin (HbA1c) and for LTBI using the QuantiFERON-TB Gold in Tube (QFT-GIT). Demographic, socioeconomic, clinical and laboratorial data were also assessed. Among 553 included participants, 88 (15.9%) had QFT-GIT positive test, of which 18 (20.5%) were non-DM, 30 (34.1%) T1D and 40 (45.4%) T2D. After adjustments for potential baseline confounders, age, self-reported non-white skin color and an active TB case in the family were significantly associated with LTBI among the studied population by using a hierarchical multivariate logistic regression analysis. Additionally, we verified that T2D patients were able to produce significant increased interferon-gamma (IFN-γ) plasma levels in response to Mycobacterium tuberculosis-specific antigens, when compared to non-DM individuals. Altogether, our data showed an increased prevalence of LTBI among DM patients, albeit non-statistically significant, and point out to important independent factors associated with LTBI, which deserve attention in monitoring patients with DM. Moreover, QFT-GIT test seems to be a good tool to screening LTBI in this population, even in a high TB burden area.